Uniquely African?: African Christian identity from cultural and historical perspectives - Cox, James L.; Haar, Gerrie ter (Religion in contemporary Africa series, 2003)
Preface : setting the context : the African Christianity project and institutional self-reflexivity / James L. Cox -- Introduction : what role do institutions of theology and religious studies play in the engagement with African cultural dynamics? / Leslie E.T. Shyllon -- African identities as the projection of Western alterity / James L. Cox -- Knowing the African : Edwin W. Smith and the invention of African traditional religion / Henk J. Van Rinsum -- Educational institutions in Igboland : Christian engagement with societal challenges / U.D. Anyanwu -- Christianity and African culture : religious challenges / Mercy Amba Oduyoye -- Christianity in a pluralistic context : religious challenges in Zimbabwe / Ezra Chitando -- Church life, civil society, and democratization in Malawi, 1992-96 / Kenneth R. Ross -- Christianity and national development in West Africa : dilemmas and possibilities / Gustav H.K. Deveneaux -- Christianity and national identity in Ghana : religious perspectives / Elom Dovlo -- Christian missions and nation building in Ghana : an historical evaluation / Robert Addo-Fenning -- 'Globecalisation' and religion : the Pentecostal model in contemporary Africa / Ogbo U. Kalu -- Old wine in new bottles : prophetic experiences in the celestial Church of Christ / Afe Adogame -- 'African' Christians or 'Christian' Africans in Europe? : issues in self-definition / Gerrie ter Haar